2018
DOI: 10.1093/ndt/gfy172
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal barrier disruption and dysregulated mucosal immunity contribute to kidney fibrosis in chronic kidney disease

Abstract: Our results suggest that intestinal dysbiosis-associated gut barrier disruption and aberrant mucosal immunity are important for the systemic inflammation and progressive fibrosis of CKD. Targeting the intestine might provide novel therapeutic opportunities for CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 39 publications
3
81
0
1
Order By: Relevance
“…Intestinal dysbiosis also occurs in chronic kidney disease (CKD) [139,140] and might actively contribute to the progression of renal failure [141,142]. The main signature of CKD dysbiosis is increased Proteobacteria [143], although increased Lachnospiraceae is also observed [140,144] (Table 2).…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…Intestinal dysbiosis also occurs in chronic kidney disease (CKD) [139,140] and might actively contribute to the progression of renal failure [141,142]. The main signature of CKD dysbiosis is increased Proteobacteria [143], although increased Lachnospiraceae is also observed [140,144] (Table 2).…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…C hanges in intestinal permeability and the intestinal microbiome have been associated with many diseases. [1][2][3][4][5] Intestinal physiology can vary, even among genetically identical animals. 6 Due to the close anatomical and physiologic connections between the intestine and the liver, there have been many studies of how changes in one affect the other.…”
mentioning
confidence: 99%
“…[31][32][33] The mucosal microbiota has close interactions with intestinal epithelial cells, as well as those of the immune system, and may have relevance for the integrity of the gastrointestinal barrier. In experimental animal models of CKD, it has been shown that gastrointestinal permeability is increased with CKD, [34][35][36] and markers of intestinal permeability are inversely correlated with estimated glomerular filtration rate in patients with CKD. 37,38 Of practical relevance for patients is that an endoscopy is required for obtaining mucosa-associated microbes.…”
Section: Sampling and Processing Effectsmentioning
confidence: 99%